Kualitas Spermatozoa Sapi Bali Polled setelah Pemberian Pakan Tersuplementasi Taoge (Phaseolus radiatus L.) - Gustina, Sri; Hasbi, Hasbi; Sonjaya, Herry; Baco, Sudirman; Qhatimah, Husnul; Saputra, Wandi; Mutmainna, Mutmainna; Kaiin, Ekayanti Mulyawati; Maulana, Tulus (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2024)
The study aimed to increase the sperm quality of polled Bali bulls with the supplementation of bean sprout (Phaseolus radiatus L.) in feeding. This research was used two polled Bali bulls aged 5-6 years old and supplemented with bean sprout 1 kg/bull two times in a week for two months. Semen was collected using artificial vagina method. The evaluation macroscopic of semen was volume while the microscopic evaluation such as motility, viability, abnormality, plasma membrane integrity (PMI), acrosome integrity, and DNA fragmentation. The result of this research showed that semen volume and spermatozoa abnormality of fresh semen after feeding of bean sprouts were not significantly difference (P>0.05) compared to before feeding, but motility and viability were significantly higher (P<0.01). Motility and acrosome integrity of frozen semen were not significantly difference (P>0.05) while viability and PMI were significant higher (P<0.01), abnormality and DNA Fragmentation were significant lower (P<0.01) after feeding compared to before. The research revealed that the supplementation of bean sprouts could increase the motility and viability but had no effect on volume and abnormality of fresh semen. Meanwhile in frozen semen, it increased viability and PMI and decreased abnormality and DNA fragmentation but had no effect on motility and acrosome integrity.